Finite size effects on the electrical properties of sol-gel synthesized CoFe2O4 powders: deviation from Maxwell-Wagner theory and evidence of surface polarization effects - George, Mathew; Nair, Swapna S.; Malini, K. A.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Physics D-Applied Physics, 2007)
Fine particles of cobalt ferrite were synthesized by the sol-gel method. Subsequent heat treatment at different temperatures yielded cobalt ferrites having different grain sizes. X-ray diffraction studies were carried out to elucidate the structure of all the samples. Dielectric permittivity and ac conductivity of all the samples were evaluated as a function of frequency, temperature and grain size. The variation of permittivity and ac conductivity with frequency reveals that the dispersion is due to Maxwell-Wagner type interfacial polarization in general, with a noted variation from the expected behaviour for the cold synthesized samples. High permittivity and conductivity for small grains were explained on the basis of the correlated barrier-hopping model.